Activity of propyl p-benzoyloxybenzoate as mu-class glutathione s-transferase inhibitor - Agnes Nora Iska Harnita; Enade Perdana Istyastono; Sudibyo Martono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the most prescribed medicines. Anti-inflammatory activity was reported to have relationship with the inhibition of prostaglandin synthesis, one of the inflammation mediators. The inhibition mechanism might be through the cyclooxygenase (COX) inhibition, oxygen radical scavenging, and mu-class glutathione S-transferase (GST) inhibition. Aspirin has been used as a NSAID since a hundred years ago and was reported as cyclooxigenase-1 (COX-1) selective inhibitor. The selectivity leds to gastrointestinal ulceration. Propyl p-benzoyloxybenzoate was a new compound which was predicted to have anti-inflammatory activity and would be developed to be an NSAID with minimum side effect.mu-class GST inhibition was examined using formation reaction model of GS-CNB conjugate through conjugation of 1,2-dichloro-4-nitrobenzene (DCNB) and glutathione (GSH) with GST (prepared from rat’s liver) as a catalyst. GSTs were isolated from the rat liver cytosolic fraction by centrifugation according to Lundgren. Protein concentration of the cytosol was determined spectrophotometrically by using bovine serum albumin as a standard. The GST activity was determined using conjugation reaction rate between DCNB and GSH, followed by determination of IC50 of propyl p-benzoyloxybenzoate. The result showed that propyl p-benzoyloxybenzoate has activity as mu-class GST inhibitor with IC50 = 111.77 μM as the result from extrapolation.Key words: Anti-inflammatory, propyl p-benzoyloxybenzoate, inhibitor, mu-class glutathione S-transferase (GST).